2020
DOI: 10.1093/conphys/coaa076
|View full text |Cite
|
Sign up to set email alerts
|

Sub-lethal effects of permethrin exposure on a passerine: implications for managing ectoparasites in wild bird nests

Abstract: Permethrin is increasingly used for parasite control in bird nests, including nests of threatened passerines. We present the first formal evaluation of the effects of continued permethrin exposure on the reproductive success and liver function of a passerine, the zebra finch (Taeniopygia guttata), for two generations. We experimentally treated all nest material with a 1% permethrin solution or a water control and provided the material to breeding finches for nest building. The success of two consecutive clutch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…Our study strongly suggests that in both nest cotton amounts and doses of permethrin (0.1% or 1%), permethrin solution crossed the shell to have non‐lethal but adverse effects on embryonic development. Although we did not measure the concentration of permethrin in our embryos, other studies have documented the presence of permethrin in the eggs of both wild birds and poultry 32,40,41 . Overall, we found embryos chronically exposed to permethrin at these doses were smaller, displayed microcephaly and changes in brain morphology, and had delayed cardiovascular development, which is largely consistent with previously reported effects of permethrin exposure on skeletal, brain, and cardiac muscle development in both avian and rodent models.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Our study strongly suggests that in both nest cotton amounts and doses of permethrin (0.1% or 1%), permethrin solution crossed the shell to have non‐lethal but adverse effects on embryonic development. Although we did not measure the concentration of permethrin in our embryos, other studies have documented the presence of permethrin in the eggs of both wild birds and poultry 32,40,41 . Overall, we found embryos chronically exposed to permethrin at these doses were smaller, displayed microcephaly and changes in brain morphology, and had delayed cardiovascular development, which is largely consistent with previously reported effects of permethrin exposure on skeletal, brain, and cardiac muscle development in both avian and rodent models.…”
Section: Discussionsupporting
confidence: 90%
“…Although we do not know whether the developmental delays shown by our study can be compensated for after hatching, the changes that we observed could very well affect post‐hatching survival. In a similar study in which 1% permethrin was added to nest material of zebra finches, hatchling mass was reduced but fledgling mass did not differ 32 . This compensatory growth may have been a result of increased parental feeding in this study, but there could be a difference in the effect of permethrin exposure with life history of the bird.…”
Section: Discussionmentioning
confidence: 40%
See 2 more Smart Citations
“…The larvae then feed externally on the blood of nestlings [26]. Larvae of P. sialia can be experimentally removed using insecticidal sprays that do not negatively impact bird nestlings survival [27][28][29]. In a related study, the interaction of elevated nest temperature and parasitism was shown to have physiological effects on eastern bluebirds and tree swallows.…”
mentioning
confidence: 99%